The Representation of Women’s Empowerment Depicted in the Movie Raya and The Last Dragon (2021) - Feronica Ambarwati (Metaphor, 2022)
The purpose of this research are to analyze the representation of women empowerment and find the impact of women empowerment in the movie Raya and The Last Dragon (2021). In this research, the researcher analyzes the women empowerment and the impact of women empowerment. Then the researcher explains the women empowerment on the main character represented in Raya and The Last Dragon (2021). The object and data of this thesis is the movie entitled Raya and The Last Dragon(2021). The researcher uses women empowerment by Rowland and Kate Young as the grounded theory. Furthermore the researcher uses semiotic analysis method by Roland Barthes and the researcher uses feminism approach to analyze the data. This research is using descriptive qualitative method. As the result, the researcher found that the impact of women empowerment on the main character is having control, or gaining further control, having a voice to be listened, being able to define and create from a women’s perspective being able to influence social choices and decisions affecting the whole society (not just areas of society accepted as women’s place), being recognized and respected as equal citizens and human beings with a contribution to make. By that finding, it is proven that the impact of women empowerment have significant effect on the main character in this movie.